A RETROSPECTIVE ANALYSIS OF REPORTED CUTANEOUS ADVERSE DRUG REACTIONS IN A TERTIARY CARE TEACHING HOSPITAL - PACKIASEELI S, PAULINE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Analysis of adverse drug reactions (ADR) reports enriches and updates physician’s awareness about the pattern of cutaneous adverse reactions in the population studied and may play an important role to envision the frequency of appearance of reactions to specific drugs and morphological designs. This study intends to portray the clinical profile and causative agents of dermal ADRs in our population. Methods: All the ADR reporting forms received from February 2021 to February 2023 were scrutinized, and forms with cutaneous ADRs (CADRs) were analyzed. The data about the history of drug intake, names of the drug taken, time lag of appearance of reaction, and clinical examination details were collected from the reports. Demography, prevalence, reaction time morphological pattern, and causative agents of CADRs were evaluated. Results: Among the CADRs, acute urticaria 53.4 was the most common followed by acute exanthematous reaction 35.8% and lichenoid drug eruption 3.8%. Among the drugs causing CADRs, antibiotics top the list with 47% followed by ATT at 29.7% and iron sucrose 12.9%. Among the antimicrobials, fluoroquinolones 48% top the list followed by cephalosporins 21.6% and penicillins and vancomycin each 8.3%. Conclusion: Physician’s knowledge about pattern and causative agents of CADR in the specific population can aid in prevention and early management of ADRs and thereby reducing hospitalization.